2021
DOI: 10.21037/jovs-20-125
|View full text |Cite
|
Sign up to set email alerts
|

Total arch replacement in the treatment of acute type A aortic dissection

Abstract: The role of total arch replacement (TAR) in patients with acute type A aortic dissection (ATAD) has been much debated. There are numerous factors that contribute to the clinical decision-making process.These include patient cohort, clinical status of the patient, aortic anatomy, dissection morphology, and expertise of the surgeon and the center. In this review, we summarize early and late outcomes of TAR in ATAD patients and discuss the specific patient populations that may benefit from an aggressive surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…(19,20) Hybrid EAR with a frozen elephant trunk (FET) has become a popular and promising option for patients in need of aortic arch repair. (17,21,22) Single-center studies have indicated long-term benefits of this approach without increasing perioperative risks. The evidence supports the use of hybrid EAR as a diverse and effective alternative to traditional arch replacements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(19,20) Hybrid EAR with a frozen elephant trunk (FET) has become a popular and promising option for patients in need of aortic arch repair. (17,21,22) Single-center studies have indicated long-term benefits of this approach without increasing perioperative risks. The evidence supports the use of hybrid EAR as a diverse and effective alternative to traditional arch replacements.…”
Section: Introductionmentioning
confidence: 99%
“…(14)(15)(16)(17)(18) However, while technology has advanced, there are still concerns regarding the technical complexity, duration of cardiopulmonary bypass (CPB), and circulatory arrest. Furthermore, there is evidence of wide variability in outcomes from center to center, and a recent meta-analysis suggested that EAR approaches may be associated with increased perioperative mortality (13)(14)(15)(16)(17)(18)(22)(23)(24). It is important to acknowledge these issues and work towards finding solutions that benefit all parties involved.…”
Section: Introductionmentioning
confidence: 99%